Acute Zika virus infection in an asymptomatic blood donor at the onset of the Puerto Rico epidemic. Issue 10 (13th August 2019) - Saa, Paula; Chiu, Charles; Grimm, Kacie; Yu, Guixia; Benjamin, Richard J.; Corash, Laurence; Stramer, Susan L.
Abstract : BACKGROUND: Zika virus (ZIKV) spread to Puerto Rico likely originated from southeastern Brazil approximately 8.5 months earlier than blood donation screening for ZIKV was initiated, but the time of ZIKV introduction in the blood donor population remains unknown. METHODS: To better understand when arboviral infections first appeared in the blood donor pool in Puerto Rico, we retrospectively screened for ZIKV RNA (as well as chikungunya [CHIKV] and dengue [DENV] viral RNA) a repository of 1186 linked blood donor and recipient samples collected from February 2015 to May 2016 as an endpoint efficacy measure following the introduction of platelet pathogen reduction (PR). Phylogenetic analysis identified relatedness of donor strain to other circulating strains, and molecular clock analysis identified the estimated time of introduction. RESULTS: An asymptomatic donor collected in December 2015 was ZIKV RNA confirmed positive, 4 months BEFORE investigational nucleic acid testing (NAT) implementation in April 2016, coincident and related to the first reported autochthonous cases. No CHIKV RNA or DENV RNA reactives were identified in donors or recipients, and no adverse events were reported from PR use in recipients. Phylogenetic analysis confirmed the molecular relatedness of the donor ZIKV strain to the Puerto Rico lineage likely introduced approximately 4.5 months earlier. CONCLUSION: This study identified an asymptomatic ZIKV infection in a blood donor occurring before those previously recognized by blood donation screening. NAT and PR continue to be used as acceptable strategies to prevent transfusion‐transmitted arboviral infections worldwide; however, repeated arboviral outbreaks warrant consideration of PR as a more proactive approach.